2021
DOI: 10.1111/pai.13477
|View full text |Cite
|
Sign up to set email alerts
|

Stay at home’: Is it good or not for house dust mite sensitized children with respiratory allergies?

Abstract: Background Lockdown was imposed for children for 75 days in Turkey to limit the spread of COVID‐19. During this period, children have to stay indoors, which might probably increase their exposures to indoor allergens and pollutants. Besides, reduced exposures to respiratory tract infections and outdoor pollutants might be favorable outcomes of this lockdown period. We evaluated the effects of the lockdown on house dust mite (HDM)–sensitized children with respiratory allergies. Methods Three‐month clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…), has been documented in spring 2020, compared to spring 2019 (9). Similar results have been demonstrated by Yucel et al (10) in a group of children with rhinitis and / or bronchial asthma with or without sensitization to dust mites. In the other hand, a substantial improvement in asthma symptoms (assessed by Asthma Control Test, drug use, frequency of exacerbations, etc.)…”
Section: -Respiratory Allergy: Effects In Indoor Environmentssupporting
confidence: 83%
See 2 more Smart Citations
“…), has been documented in spring 2020, compared to spring 2019 (9). Similar results have been demonstrated by Yucel et al (10) in a group of children with rhinitis and / or bronchial asthma with or without sensitization to dust mites. In the other hand, a substantial improvement in asthma symptoms (assessed by Asthma Control Test, drug use, frequency of exacerbations, etc.)…”
Section: -Respiratory Allergy: Effects In Indoor Environmentssupporting
confidence: 83%
“…However, in children with associated mite allergic rhinitis it has been showed a significant increase in the severity of nasal and conjunctival symptoms in the period March-May 2020, compared to the same months of 2019. No significant increase in the same nasal/ocular symptoms was reported in subjects with asthma and nonallergic rhinitis (10).…”
Section: -Respiratory Allergy: Effects In Indoor Environmentsmentioning
confidence: 59%
See 1 more Smart Citation
“…In the period of lockdown, allergic patients inevitably remained more confined to the home environment. Yucel et al (52) raised the question of relapses in patients allergic to HDM. This study carried out during 75 days of lockdown on 81 children showed an improvement in lung function and consequently in asthma symptoms, probably due to the reduction of respiratory tract infections and M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n exposure to outdoor pollution.…”
Section: Younger Age And/or Absence Of Comorbiditiesmentioning
confidence: 99%
“…Indeed, increasing evidence has shown that the exposure of children to environmental indoor stressors is associated with respiratory conditions including wheezing, asthma, and rhinitis ( 62 ). It should also be pointed out that co-exposure to indoor allergens may aggravate airway inflammation, resulting in worsening of symptoms in sensitized children ( 63 ). The multifactorial routes of exposure to indoor pollutants should therefore be considered, also with a view to future confinement episodes for possible new waves of SARS-CoV-2.…”
Section: Performing Physical Activity At Home During the Covid-19 Pandemic: The Issue Of Indoor Air Qualitymentioning
confidence: 99%